AI-Powered Storybooks: An Interactive Medium for Early Childhood English Literacy - Roza, Desmawati; Sharif, Qaisar (Educative: Jurnal Ilmiah Pendidikan, 2026)
The integration of artificial intelligence (AI) into educational materials has opened new possibilities for early childhood language learning. This study aimed to develop and evaluate an AI-based interactive storybook as a medium for introducing English vocabulary to early childhood learners at TK Yayasan Wanita Kereta Api (YWKA). Employing a Research and Development (R&D) approach with the ADDIE model on a limited scale, the study involved 20 children from one classroom. Data were collected through structured observation using a four-point developmental rubric assessing vocabulary recognition, word-picture association, pronunciation, listening engagement, and comprehension. Results indicated that the majority of children achieved the Developing as Expected (BSH) and Developing Very Well (BSB) categories across all indicators. The AI-based storybook proved effective in enhancing children's English vocabulary acquisition and sustaining learning engagement throughout the instructional process. These findings conclude that AI-based storybooks represent a viable and innovative instructional medium for early childhood education. The implications suggest that such technology-enhanced materials should be more widely integrated into early childhood curricula, particularly to introduce English language learning at an early age, thereby supporting the development of foundational language competencies in young learners.